Does terminology matter when measuring stigmatizing attitudes about weight? Validation of a brief, modified attitudes toward obese persons scale - Caitlin A. Martin‐Wagar; Katelyn A. Melcher; Sarah E. Attaway; Brooke L. Bennett; Connor J. Thompson; Oscar Kronenberger; Taylor E. Penwell (Wiley, 2024)
Abstract Objective Commonly used terms like "obese person" have been identified as stigmatizing by those with lived experience. Thus, this study sought to revise a commonly used measure of weight stigmatizing attitudes, the Attitudes Toward Obese Persons (ATOP) scale. Methods The original terminology in the 20‐item ATOP (e.g., "obese") was compared to a modified version using neutral terms (e.g., "higher weight"). Participants (N = 832) were randomized to either receive the original or modified ATOP. Results There was a statistically significant difference, with a small effect size (d = −0.22), between the scores of participants who received the original ATOP (M = 69.25) and the modified ATOP (M = 72.85), t(414) = −2.27, p = 0.024. Through principal component analysis, the modified ATOP was best used as a brief, 8‐item unidimensional measure. In a second sample, confirmatory factor analysis verified the fit of the brief, 8‐item factor structure. Conclusions Findings suggest that a modified, brief version of the ATOP (ATOP‐Heigher Weight; ATOP‐HW) with neutral language is suitable for assessing negative attitudes about higher‐weight people. The ATOP‐HW may slightly underestimate weight stigma compared to the original ATOP, or the language in the ATOP may magnify negative attitudes. Further examination of the terminology used in weight stigma measures is needed to determine how to best assess weight stigma without reinforcing stigmatizing attitudes. The present study's findings suggest that the use of neutral terms in measures of anti‐fat bias is a promising solution that warrants further investigation.